Strategic Management and Organisational Dynamics: The Challenge of Com plexity - Stacey, Ralph D. (Pitman, 2000)
In the third edition of this successful text, Ralph Stacey continues t o question the view that organisations operate and succeed in relative ly stable environments. He argues that in order to succeed in uncertai nty and continual change, organisations need to create new perspective s and learn from the chaos within which they operate. This edition con tinues to focus on this radically different approach to strategic mana gement. The central tenets of this approach have to do with unpredicta bility and the limitations of control, and therefore it argues against the rational models of planning and control covered in other strategy textbooks. This is done by emphasising the importance of narrative, c onversation and learning from one's own experience as the central mean s by which we can gain understanding and knowledge of strategy in orga nisations. - Sharper distinction between systemic and process thinking with new chapters on the philosophical origins of systems and process thinking, second order and critical system thinking. - new material o n theory of complex responsive processes, particularly to do with cont rol, leadership and ethics. - Includes 7 management narratives, ie, pe rsonal ac
Keywords: Organizational Behavior; Strategic Planning